The Relationship Between Celebrity Worship and Body Image in Female Students Who Are K-POP Fans at Makassar State University - Ningsih, St Hardiati; Firdaus, Faradillah; Akmal, Nur (Polteknik Ilmu Pemasyarakatan, 2024)
This study aims to determine the relationship between celebrity worship and body image in female K-pop fans at Makassar State University. This research uses quantitative methods with accidental sampling techniques. Respondents in this study were female K-pop fan students at Makassar State University totaling 210 people. The measuring instruments used are the Celebrity Adoration Scale and the Body Image Scale. Data were collected through questionnaires distributed online. The data were analyzed using the Pearson Product Moment analysis technique with the help of the SPSS v.22 application. Based on the results of data research, the correlation coefficient value is r = 597 and p = 0.000 which shows that there is a significant positive relationship between celebrity worship and body image in female K-pop fans at Makassar State University. This study indicates that the higher the celebrity worship score, the higher the body image of female K-pop fans at Makassar State University.